A Klebsiella variicola Plasmid Confers Hypermucoviscosity-Like Phenotype and Alters Capsule Production and Virulence - Rodríguez-Medina, Nadia; Martínez-Romero, Esperanza; De la Cruz, Miguel Angel; Ares, Miguel Angel; Valdovinos-Torres, Humberto; Silva-Sánchez, Jesús; Lozano-Aguirre, Luis; Martínez-Barnetche, Jesús; Andrade, Veronica; Garza-Ramos, Ulises (Frontiers in Microbiology, 2020)
Hypermucoviscosity (hmv) is a capsule-associated phenotype usually linked with hypervirulent K. pneumoniae strains. The key components of this phenotype are the RmpADC proteins contained in non-transmissible plasmids identified and studied in K. pneumoniae. Klebsiella variicola is closely related to K. pneumoniae and recently has been proposed as an emergent human pathogen. K. variicola normally contains plasmids, some of them carrying antibiotic resistance and virulence genes. Previously, we described a K. variicola clinical isolate showing a hypermucoviscosity-like (hmv-like) phenotype that harbors a 343-kb-pKV8917 plasmid. Here, we investigated whether pKV8917 plasmid carried by K. variicola 8917 is linked with hmv-like phenotype and its contribution to virulence. We found that curing the 343-kb pKV8917 plasmid caused the loss of hypermucoviscosity; a reduction in capsular polysaccharide (CPS) (P<0.001) and virulence. In addition, pKV8917 was successfully transferred to E. coli and K. variicola strains via conjugation. Notably, when pKV8917 was transferred to K. variicola, the transconjugants displayed hmv-like phenotype, and capsule production and virulence increased; these phenotypes were not observed in the E. coli transconjugants. These data suggest that the pKV8917 plasmid carries novel hmv and capsule determinants. Whole-plasmid sequencing and analysis revealed that pKV8917 does not contain rmpADC/rmpA2 genes, thus an alternative mechanism was searched. The 343-kb plasmid contains an IncFIB backbone and shares a region of 150-kb with a 99% identity and 49% coverage with a virulence plasmid from hypervirulent K. variicola and MDR K. pneumoniae. This pKV8917-unique region harbors a cellulose biosynthesis cluster (bcs), a fructose- and sucrose-specific (fru/scr) phosphotransferase systems, and the transcriptional regulators araC and iclR, respectively, involved in membrane permeability and glyoxylate shunt and baeSR a two-component system related with envelope stress response. The hmv-like phenotype has been identified more frequently, and recent evidence supports the existence of rmpADC/rmpA2-independent hmv-like pathways in this bacterial genus.